FOLLOW-UP ADHERENCE IN PATIENTS WITH NONPROLIFERATIVE DIABETIC RETINOPATHY PRESENTING TO AN OPHTHALMIC EMERGENCY DEPARTMENT. Issue 6 (June 2021) - Watane, Arjun; Kalavar, Meghana; Vanner, Elizabeth A.; Cavuoto, Kara; Sridhar, Jayanth
Abstract : Purpose: To determine the rate of follow-up after emergent encounters for nonproliferative diabetic retinopathy and to identify patient or visit characteristics associated with follow-up adherence. Methods: A retrospective cohort study of patients presenting to an ophthalmic emergency department with nonproliferative diabetic retinopathy between May 2014 and December 2018 was conducted. Demographic and encounter data were gathered. Adherence to follow-up was defined as a completed encounter within 5 weeks of the recommended follow-up. Results: A total of 1, 248 patients were included. The overall follow-up rate was 53%. Significantly decreased odds of follow-up adherence were associated with longer physician recommended follow-up intervals (odds ratio: 0.81, P < 0.001), longer interval to scheduled appointment (OR: 0.98, P < 0.001), commercial insurance (OR: 0.76, P = 0.01), and lack of any insurance (OR: 0.57, P < 0.01). Significantly increased odds were associated with a longer emergency department visit duration (OR: 1.002, P = 0.001), farther home distance (1.02, P < 0.01), increased likelihood of living in a higher income area (OR: 1.07, P = 0.04), greater NPDR severity (OR: 1.23, P < 0.01), Medicare (OR: 1.38, P = 0.04), presence of macular edema (OR: 1.66, P < 0.001), and worse vision (OR: 1.73, P < 0.001). Conclusion: Patients presenting emergently with non-proliferative diabetic retinopathy are at high risk for follow-up nonadherence. Several patient and encounter characteristics were associated with follow-up adherence. Abstract : Supplemental Digital Content is Available in the Text.Patients presenting to an emergency department with nonproliferative diabetic retinopathy are at high risk for follow-up nonadherence. In this retrospective review, several demographic and encounter characteristics had significant effects on the odds of follow-up adherence, including visual acuity, retinopathy severity, socioeconomic status, and insurance status.